Kondisi Sosial Ekonomi Perempuan Menikah Pada Sub Sektor Perkebunan (Kelapa Sawit) Dalam Meningkatkan Pendapatan Keluarga Di Kecamatan Pinggir (Studi Kasus PT. Adei Plantation & Industry) - Gracia Gracia; Rahmita Budiartiningsih; Lapeti Sari (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2023)
The goal the researcher wants to achieve is to know the social economic condition of married women in sub sectors of palm plantations can increase family income in marginal districts (pt adei plantation & industry). The study uses primary data obtained directly from respondents (married women working in the sub- sector of palm plantations), and secondary data collected from official or governmental agencies. Data collection techniques are field research, which is field research, data collection on research sites using observation and retrieval techniques. The method of data analysis used is qualitative descriptive. The socio economic conditions of the respondents were seen from the education factor, namely the medium socio-economic condition group, women who worked as employees of the oil palm maintenance division at PT. Adei Plantation & Industry average elementary school to high school graduates. The average husband income from the bank will be up to per share, as is the wages paid by women who work as employees of the palm oil plants at the state of bengkalis is already able to provide for the daily needs of the family. The average number of loads owned by the respondents at the number children, as many as for the age of respondents there is a level of productive where there are as many as and famale workers receive fulfillment of their rights to menstruation and maternity.